Kecerdasan Emosi Ditinjau Dari Keikutsertaan Dalam Program Meditasi - Adya Baskara; Helly P. Soetjipto; Nuryati Atamimi (Jurnal Psikologi, 2008)
This  study  was  aimed  to  see  the difference  between  emotional  intelligence  of those  who  participated  in  meditation program and those who did not. The subjects of this study were university students. The subjects were divided into 3 groups:meditators who were currently participating in meditation program for 1‐6 months, meditators who were currently participating in meditation program for more than 6 months, and non‐meditators. Each group consisted 30 subjects. Anova analysis resulted a coefficient of F = 34. 703, and p < 0.01. The results indicated that there was a difference in emotional intelligence between the 3 groups. Meditators who participated in meditation for more than 6 months had higher emotional intelligence than those who had only participated for 1‐6 months, and non‐meditators. There was no difference in emotional intelligence between those who had only participated for 1‐6 months and non‐meditators.